FUSE observations towards the pole-on Be star HR 5223 - Frémat, Yves (2002)
New spectra have been obtained for the pole-on Be star HR 5223 (HD 120991) using the Far Ultraviolet Satellite Explorer (FUSE). We give a complete description of the far-UV spectral range (920 to 1180 Å). The spectra are affected by strong blends with interstellar lines and molecular bands that also significantly lower the energy distribution of the star. We produce a synthetic spectrum of the interstellar medium (ISM) to determine the column densities of several elements (H2, H I, N I, O I ...) seen towards HR 5223 and to disentangle the components due to the ISM, the photosphere and/or to the circumstellar envelope. The line identification list is available at the CDS. Using the obtained column densities, we determine the reddening of the star due to the ISM only and locate the star relative to the nearby IS clouds. The fit of the dereddened UV flux distribution with models that account for the gravitational darkening due to the stellar fast rotation allowed us to estimate the stellar fundamental parameters (Teff = 22 000 K; log g = 3.7) and its distance (d = 834 ± 20 pc). The distance obtained, which has to be considered as the most accurate available at the moment, is in agreement with the characteristics of the ISM matter distribution that affects the observed spectrum of the star and with the detecting limits of the HIPPARCOS satellite.